Reprocessable and Recyclable Crosslinked Polyethylene with Triple Shape Memory Effect. Issue 3 (27th December 2018) - Ji, Fance; Liu, Xiangdong; Lin, Changhong; Zhou, Yan; Dong, Li; Xu, Shaobin; Sheng, Dekun; Yang, Yuming
Abstract: Thermosetting polymers, such as epoxy resins, have found widespread applications because of their excellent thermomechanical and solvent resistance properties. However, the recycling of thermosets remains a challenge, due to the irreversible covalent crosslinking bonds in the network. The exchangeable covalent bonds in vitrimers open opportunities in the way that materials can be dynamically repaired. However, in the case of polyolefins, the strategy of exchangeable vitrimers is still underexplored. Herein, a simple way is reported to prepare a high‐density polyethylene (HDPE) vitrimer with a triple shape memory effect, where exchangeable esters are introduced into the network of covalently crosslinked HDPE. With the incorporation of polyethers or polyesters into the crosslinked network, the two obtained vitrimers show outstanding recyclability and a good triple shape memory effect. This new strategy of preparing an HDPE vitrimer might allow the high‐value utilization of crosslinked polyolefins. Abstract : A simple way is reported to prepare a high‐density polyethylene (HDPE) vitrimer with triple shape memory effect, where exchangeable esters are introduced into the network of covalently crosslinked HDPE. With the incorporation of polyethers and polyesters into the crosslinked network, both the obtained vitrimers show outstanding recyclability and a good triple shape memory effect.